2016
DOI: 10.1039/c5ra23181g
|View full text |Cite
|
Sign up to set email alerts
|

Insights on the combustion and pyrolysis behavior of three different ranks of coals using reactive molecular dynamics simulation

Abstract: The process of combustion and pyrolysis of coal can be considered to be convoluted where numerous intermediates are expected to form during the course of the reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…An alternative way is to obtain meaningful and accurate data based on Reactive Force Field simulations. In our earlier work [47] we have depicted the reaction mechanism using ReaxFF simulation at a temperature of 3000 K in fuel rich condition. From the simulations, it was confirmed that the formation of CO is essentially due to the breakage of carbon-carbon (\ \C\ \C\ \) chain within the coal molecule.…”
Section: Aromatic Hydrocarbon Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative way is to obtain meaningful and accurate data based on Reactive Force Field simulations. In our earlier work [47] we have depicted the reaction mechanism using ReaxFF simulation at a temperature of 3000 K in fuel rich condition. From the simulations, it was confirmed that the formation of CO is essentially due to the breakage of carbon-carbon (\ \C\ \C\ \) chain within the coal molecule.…”
Section: Aromatic Hydrocarbon Groupsmentioning
confidence: 99%
“…However, quantifying their effect is very difficult as numerous intermediates are known to form during fractionation. Hence interaction of coal and ILs was performed by using both Molecular Dynamics [47] and COSMO-RS [30] simulations. This interaction causes an increase of swelling ratio because of the formation of other inclusive compounds [29].…”
Section: Morphology Of Raw Coal and Five Different Il-pretreated Coalsmentioning
confidence: 99%
“…The ensemble of generated velocities corresponds to a gaussian distribution with a mean of 0.0 and a sigma scaled to produce the requested temperature in this work. Note that a higher temperature (1500-3000 K) is usually adopted in the ReaxFF MD simulation to visualize the pyrolysis process within a computationally affordable time [36]. The Nosé -Hoover thermostat with a damping constant of 100 fs is adopted to control the system temperature.…”
Section: Reaxff MD Simulationsmentioning
confidence: 99%
“…Lee et al [16] examined the pore structure variation of coal char during pyrolysis and concluded the higher surface area and better dispersion of ash phase leads to a higher combustion reactivity of the Shievee Ovoo coal (SOC) char. More recently, Bhoi et al [17] and Gao et al [18] adopted ReaxFF molecular dynamics simulations to investigate coal pyrolysis at a microscopic view. Meanwhile, the pyrolysis, as part of the coal conversion technology, can extract high-value parts in coal to the gaseous fuel, liquids, and the coke.…”
Section: Introductionmentioning
confidence: 99%